Determinants of Labour Complication in Indonesia (2017 IDHS Data Analysis) - Tiarasari, Intan; Melania Hidayat; Fahmi Ichwansyah; Nurjannah; Asnawi Abdullah; Aryandi Darwis (STRADA : Jurnal Ilmiah Kesehatan, 2023)
An inconclusive fetal condition, or what is known as fetal distress, is one of the birth complications that needs attention, such as irregular heartbeat, low amniotic fluid and asphyxia. The aim of this study was to determine factors associated with pregnancy complications. This study is an analysis of secondary data from the 2017 IDHS (Indonesian Health Demographic Survey 2017). The design of this research is a cross-sectional studyThe sample in this study had 49,627 inclusion and exclusion criteria. The data was analyzed using logistic regression. the results of this research a relationship between maternal age in the high risk category, maternal education in the low category, parity in the high category, utilization of antenatal care is in the bad category, the use of family planning in the non MKJP category and having pregnancy complications with delivery complications.